Studying the Creative Works of Nosir Fozilov in School Textbooks - Babarakayev, Rahmatulla; Musaeva, Shakhlo Kudratovna (Central Asian Journal of Literature, Philosophy and Culture, 2022)
Books are one of the main factors in educating young people as mature people. Children’s literature is a collection of artistic, scientific, popular and journalistic works created for children and teenagers. Children’s literature includes examples of oral creativity, mostly created for children, such as rhymes, riddles, game songs, narratives, legends, fairy tales, proverbs, parables, and epics. Uzbek children’s literature has developed under the influence of advanced traditions of world children’s literature. This article highlights the creative works Nosir Fozilov who is one of the writers of Uzbek children’s literature.